Morphological variability in Polygenis (Polygenis) platensis (Jordan & Rothschild) (Siphonaptera: Rhopalopsyllidae: Rhopalopsyllinae) and taxonomic consequences - Lareschi, Marcela; Linardi, Pedro M. (Zootaxa, 2009)
There are two subspecies of the flea Polygenis (Polygenis) platensis (Jordan & Rothschild). We analyzed characters which are considered diagnostic of males and females of these subspecies, including length of the setae of the hind tibia and hind tarsal segments, the number of setae on the basal abdominal sternum, and the number of setae on the outer surface of the hind femur. In females, the shape of the ventral margin of the bulga of the spermatheca and in males, the number of convolutions of the coil of aedeagal tubus inferior were also examined. There was great variation in every characteristic observed, independent of locality of collection and host taxonomic group. However, a combination of the different states of the characters, as presented in the original descriptions of the subspecies and in keys in the literature, was not observed. Therefore, we state that there is no evidence for the maintenance of these two taxa as separate subspecies, and Polygenis platensis cisandinus is considered a synonym of P. (P.) platensis platensis syn.n.